Impactos ambientais e soluções sustentáveis para o descarte de máscaras faciais descartáveis: reciclagem e redesign - Nardini, Larissa Batista (Universidade Federal de São Carlos, 2025)
The COVID-19 pandemic has increased the production and use of disposable face masks made of non-woven fabric. Although essential for health control, their improper disposal has caused significant environmental impacts, such as the increase in microplastics in terrestrial and aquatic ecosystems. This study reviews all the environmental impacts caused by the improper disposal of masks and, consequently, the challenges for recycling. This study provides a review of the complete composition of the mask, indicating that it is a material composed of different polymers, namely polypropylene, polyethylene terephthalate, polyethylene and polyurethane, and the presence of a metal found in the moldable region of the nose. Therefore, with the complex and variable composition of the mask, attempts to recycle it result in an immiscible and incompatible blend, which makes the process even more difficult. Therefore, the solution to this problem may be the redesign and production with a single component, polypropylene. This study concludes that, to mitigate environmental impacts, it is essential to integrate more efficient recycling strategies and processes, thus reducing pollution caused by the improper disposal of disposable masks.
Environmental impacts and sustainable solutions for the disposal of disposable face masks: recycling and redesign
Keywords: Impacto ambiental; Máscaras faciais descartáveis; Reciclagem; Redesign; CIENCIAS EXATAS E DA TERRA::QUIMICA